Faktor – Faktor yang Memengaruhi Purchase Intention Produk Kosmetik di Jakarta - Hergian Stephanie; Rodhiah (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study is to examine and discuss the effect of environmental knowledge, word of mouth, green marketing and attitude towards brands on purchase intention. The population used in this study are people who know and use cosmetics products in Jakarta. This study used a quantitative descriptive method and managed to collect a sample of 217 respondents with criteria, namely at least 18 years old and above, respondents who know and use. The total number of respondents used was 207 respondents, because 10 respondents did not meet the predetermined criteria. This research uses and implements non-probability sampling using purposive sampling method. Accompanied by collecting data by distributing questionnaires online through the google form application. The results of the data that have been distributed and then collected for analysis purposes using the SmartPLS 4.1 application with the Partial Least Square Structural Equation Modeling (PLS-SEM) model. The results of this analysis show that the position of environmental knowledge, word of mouth, green marketing and attitude towards the brand have a positive and significant impact on purchase intention. In addition to its contribution in the academic field, this research is expected to provide benefits for cosmetics companies or other companies in increasing consumer purchase intentions through the various variables discussed in this study. This research Keywords: Environmental knowledge, word of mouth, green marketing, brand attitude, purchase intention